2021
DOI: 10.3390/su13126915
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Governance on the Intention of Medical Tourism in Uzbekistan

Abstract: Medical tourism is a growing niche market with huge potential as the 6th industry of medical services, including an unforgettable trip. Due to these advantages, Uzbekistan hopes to be a leader in central Asia concerning medical tourism. Contrary to this ambitious goal, Uzbekistan patients still prefer going abroad for medical services. Therefore, in order for Uzbekistan to be a hub for medical tourism, the sustainable governance factors of medical tourism need to be found for local patients going overseas. Und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Such incidents cause an inclination to opt for domestic providers and a decreased reliance on foreign or outbound medical tourism. Choi et al (2021) also found the effect of perceived value and satisfaction on customers' behavioural orientation. As patients mostly travel because of a lack of satisfaction and trust in domestic health-care provision, customer satisfaction and trust in domestic clinics and physicians negatively influence a patient's travel intent (Chia and Liao, 2021).…”
Section: Hypothesis Developmentmentioning
confidence: 86%
See 1 more Smart Citation
“…Such incidents cause an inclination to opt for domestic providers and a decreased reliance on foreign or outbound medical tourism. Choi et al (2021) also found the effect of perceived value and satisfaction on customers' behavioural orientation. As patients mostly travel because of a lack of satisfaction and trust in domestic health-care provision, customer satisfaction and trust in domestic clinics and physicians negatively influence a patient's travel intent (Chia and Liao, 2021).…”
Section: Hypothesis Developmentmentioning
confidence: 86%
“…Such incidents cause an inclination to opt for domestic providers and a decreased reliance on foreign or outbound medical tourism. Choi et al . (2021) also found the effect of perceived value and satisfaction on customers’ behavioural orientation.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…For this reason, the low cost of medical treatments is one of the main factors to attracting dental visitors (Cortez, 2008; Moschis & Chambers, 2009). In this sense, the perceived value of both the medical trip and the treatment by customers is a strategic priority in the dental tourism sector because it positively affects the RI (Keshavarz & Jamshidi, 2018; Cham et al, 2020; Habibi & Rasoolimanesh, 2020; Choi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The creation of value perceived by customers is a strategic priority in the medical tourism sector, because it positively affects repurchase intention (Keshavarz & Jamshidi, 2018). Likewise, the perceived value of both the medical trip and the treatment results in positive behavioral intentions to repurchase (Cham et al, 2020;Habibi & Rasoolimanesh, 2020;Choi, Ashurova, & Lee, 2021). Despite this tendency, Alhidari & Alkadhi (2018) concluded that price does not influence repurchase intention or loyalty.…”
Section: 21mentioning
confidence: 99%
“…Unfortunately, the conclusions of their research did not match with the reality of their research subjects of governments and industries simply because most of these research papers could not find any missing links in the governance of the policies or strategies. Here, governance is defined as a work-able mechanism for the sustainable performance of economic agents, such as a government or industry [6]. Even though they confirmed their efforts towards E&E issues, there was not significant improvement in any country in the world in even the most successful cases of E&E because all of the economic agents continue to use the traditional paradigm to solve E&E issues; thus, all of these efforts may conflict against their ultimate purpose of economic success.…”
Section: Challenges Of Energy and Urbanization Issuesmentioning
confidence: 99%